2020
DOI: 10.31089/1026-9428-2019-59-9-601-602
|View full text |Cite
|
Sign up to set email alerts
|

Hygienic criteria of monitoring system to identify workers with early signs of occupational diseases

Abstract: The results of the assessment of the impact of risk factors on the health of workers of the mining and processing plant are presented. The necessity to take into account the high relative risk of developing diseases of the musculoskeletal system, as well as diseases of the circulatory system in the system of monitoring the detection of workers with early signs of occupational diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The occurrence of health risk to miners is assessed through surveys of their working conditions, which evaluate temperature, humidity, and air velocity in the workplace. Works [4,5,6] describe a number of diseases and pathologies, the development of which is promoted by prolonged exposure to a cooling microclimate. It has been observed that even brief hypothermia can cause a reorganisation of homeostatic and regulatory systems, resulting in a decrease in immune status.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of health risk to miners is assessed through surveys of their working conditions, which evaluate temperature, humidity, and air velocity in the workplace. Works [4,5,6] describe a number of diseases and pathologies, the development of which is promoted by prolonged exposure to a cooling microclimate. It has been observed that even brief hypothermia can cause a reorganisation of homeostatic and regulatory systems, resulting in a decrease in immune status.…”
Section: Introductionmentioning
confidence: 99%